SYNTACTIC RELATIONSHIP BETWEEN THE COMPONENTS OF COMPOUND WORDS (SCIENCE TIME JOURNAL, 2026)
This article examines the syntactic relationships between the components of compound words from both theoretical and practical perspectives. The structural models of compound formations, as well as the subordinative and coordinative relations between their components, are analyzed within contemporary linguistic frameworks. The study employs structural, distributive, and componential analysis methods to reveal the internal syntactic mechanisms underlying compound units. Special attention is given to distinguishing compound words from free word combinations by identifying criteria such as morphological cohesion and semantic integrity. The findings demonstrate that syntactic relations between compound components play a significant role in the dynamic development of the language system and contribute to the enrichment of the lexical-semantic structure. The research provides a methodological foundation for further studies in theoretical linguistics, word formation, and syntax.